Die Herausforderungen der Wende – Lösungsansätze und Konsequenzen: Familienhilfe, das Modell der HÍD-Familienhilfe, kirchliche Rollenübernahme und Spiritualität in Ungarn - Csáky-Pallavicini, Roger; Pilinszki, Attila; Tomcsányi, Teodóra (European Journal of Mental Health, 2011)
Challenges Posed by the Fall of Communism – Answers and Conclusions: Family Support, the HÍD Family Support Model, the Role of the Church and Spirituality in Hungary: In the years immediately before and following the fall of communism, in a new social climate, several psychosocial issues requiring attention and solutions surfaced in Hungary. The study outlines the challenges faced at the end of the 80s and the beginning of the 90s, and also provides a glimpse of the answers developed in this social situation. The concept of the HÍD family support service, an integral part of and best practice for the nationwide family support network, is presented, in which the district council (later ‘the local government’) and the Church joined forces in order to solve psychosocial issues. The possibilities and tools of mental hygiene oriented psychosocial spiritual work are presented through a case study. Finally, conclusions are drawn.